Disease self-management in patients with moderate COPD: a thematic analysis - Molin, Katrine Rutkær (Eur Clin Respir J, 2020)
BACKGROUND: Treatment of patients with moderate chronic obstructive pulmonary disease (COPD) is challenged by the low priority of the disease by patients and general practitioners (GPs) affecting the extent of self-management. The aim of this study was to explore (i) attitudes to COPD self-management in patients with moderate COPD, (ii) perceptions of GP commitment to pulmonary rehabilitation in patients with moderate COPD, and (iii) COPD knowledge in patients with moderate COPD. METHODS: The study had a qualitative design using semi-structured interviews to explore the views of 14 patients diagnosed with moderate COPD. We applied strategic sampling to obtain maximum variation and conducted a thematic analysis of the data. RESULTS: Our main findings were that the degree of COPD self-management was linked to the resources of the informants. Further, the patients experienced that GPs only availed themselves of selected parts of the recommendations for COPD treatment by focusing on medical treatment and smoking cessation rather than physical activity and diet. Many patients lacked knowledge regarding the tolerated level of physical activity and therefore avoided activity increasing their heart rate. Finally, many patients were reluctant to accept the diagnosis because the disease is known to be self-inflicted. CONCLUSION: Our study suggests that patients with moderate COPD need more information, especially regarding the positive effects of physical activity. GPs might need to devote more time to the three main elements of COPD treatment, smoking cessation, medical treatment, and physical activity, to promote self-management and a healthier lifestyle in patients with COPD.